Blood viscosity in multiple sclerosis - Blair, G. W. Scott (1972)
Native blood from healthy subjects and from some pathological cases showed a fall in viscosity after the first passage through a stainless steel capillary viscometer in 97% of tests. Fortyfive blood samples from 27 active multiple sclerosis patients were tested. Blood from 19 of these patients showed no fall in viscosity.